Diagnostic accuracy of serological tests for the diagnosis of Chikungunya virus infection: A systematic review and meta-analysis - Anna, Andrew; Navien, Tholasi Nadhan; Yeoh, Tzi Shien; Citartan, Marimuthu; Ernest, Mangantig; Ch'ng, Ewe Seng; Tang, Thean Hock; Magdline Sia, Henry Sum (PLOS, 2022)
Background Chikungunya virus (CHIKV) causes febrile illnesses and has always been misdiagnosed as other viral infections, such as dengue and Zika; thus, a laboratory test is needed. Serological tests are commonly used to diagnose CHIKV infection, but their accuracy is questionable due to varying degrees of reported sensitivities and specificities. Herein, we conducted a systematic review and meta-analysis to evaluate the diagnostic accuracy of serological tests currently available for CHIKV.